Prevalence and predictors of anaemia in patients with HIV infection at the initiation of combined antiretroviral therapy in Xinjiang, China. (March 2015) - Mijiti, Peierdun; Yuexin, Zhang; Min, Liu; Wubuli, Maimaitili; Kejun, Pan; Upur, Halmurat
Summary: We retrospectively analysed routinely collected baseline data of 2252 patients with HIV infection registered in the National Free Antiretroviral Treatment Program in Xinjiang province, China, from 2006 to 2011 to estimate the prevalence and predictors of anaemia at the initiation of combined antiretroviral therapy. Anaemia was diagnosed using the criteria set forth by the World Health Organisation, and univariate and multivariate logistic regression analyses were performed to determine its predictors. The prevalences of mild, moderate, and severe anaemia at the initiation of combined antiretroviral therapy were 19.2%, 17.1%, and 2.6%, respectively. Overall, 38.9% of the patients were anaemic at the initiation of combined antiretroviral therapy. The multivariate logistic regression analysis indicated that Uyghur ethnicity, female gender, lower CD4 count, lower body mass index value, self-reported tuberculosis infection, and oral candidiasis were associated with a higher prevalence of anaemia, whereas higher serum alanine aminotransferase level was associated with a lower prevalence of anaemia. The results suggest that the overall prevalence of anaemia at the initiation of combined antiretroviral therapy in patients with HIV infection is high in Xinjiang, China, but severe anaemia is uncommon. Patients in China should be routinely checked for anaemia prior to combined antiretroviral therapy initiation, and healthcare providers should carefully select the appropriate first-line combined antiretroviral therapy regimens for anaemic patients.